Volatilomics and Physical Characteristics of Chicken and Pork “Urutan” (Traditional Balinese Sausage) - Andryani, Putu Cisya; Budi, Faleh Setia; Rohman, Abdul; Dachriyanus, Dachriyanus; Abu Bakar, Nor Kartini; Yuliana, Nancy Dewi (Department of Technology of Agricultural product (THP) Jambi University, 2025)
Abstract— “Urutan” is a traditional Balinese fermented sausage prepared from pork or chicken. Information on chemical and physical characteristics of “Urutan” is important, specifically for Muslims unable to consume pork. Therefore, this study aimed to characterize volatile compounds and physical properties of chicken and pork “Urutan” available in Balinese market. Volatile compounds were analyzed using Solid-Phase Microextraction Gas Chromatography-Mass Spectrometry (SPME/GC-MS) and multivariate data analysis. Physical characteristics assessed were texture, color, and water holding capacity (WHC). Multivariate analysis was conducted for the data collected to determine distinct volatile compounds as well as physical profiles of chicken and pork “Urutan”. The score plots of orthogonal projection to the least square-discriminant analysis (OPLS-DA) of volatile data showed distinct grouping among chicken and pork “Urutan”. Based on Variable Importance in Projection (VIP) scores and Correlation Coefficients, the most significant volatile markers in chicken “Urutan” were formic acid, 2,5-dimethyl-furan, and 6-methyl-tridecane, while 1-octen-3-ol, 3,6-dimethyl-octane, and 1-Octen-3-one were identified as markers of pork “Urutan”. The results of physical analysis showed significant differences between springiness, lightness, and WHC of both products. There were no significant differences between hardness, cohesiveness, gumminess, a*, and b* values. Volatilomics was found to be a more reliable method for differentiating chicken “Urutan” from pork “Urutan”, compared to using physical characteristics only.